Psychopathology history, diagnosis, and empirical foundations - Craighead, W. Edward; Miklowitz, David Jay 1957-; Craighead, Linda W. (Wiley, 2017)
"A modern take on adult disorders, incorporating context, research, and more Psychopathology provides unique, state-of-the-art coverage of adult psychopathology as categorical, evidence-based, and continuously evolving. Comprehensive coverage features a detailed examination of DSM disorders, including description, epidemiology, prevalence, consequences, neurobiological and translational research, treatment, and more, with each chapter written by an experts in the field. Mapped to the DSM-5, each chapter includes clinical case examples that illustrate how psychopathology and assessment influence treatment. This new third edition has been updated to align with the latest thinking on alcohol and substance use disorders, sleep-wake disorders, and personality disorders. Students will delve into the DSM system's limitations and strengths, and they will gain deeper insight into the historical context in which today's diagnoses are made. Advancing research continues to broaden the boundaries of psychopathology beyond traditional lines, revealing its complexity while simultaneously deepening our understanding of these disorders and how to treat them. This book goes beyond DSM descriptions to provide a comprehensive look at the whole disorder, from assessment through treatment and beyond. Review DSM-5 classifications matched with illustrative case examples Learn the neurobiological and genetic factors related to each disorder Understand related behavioral, social, cognitive, and emotional effects Delve into translational research, assessment methodologies, and treatment Contributions from specialists in each disorder provide exceptional insight into all aspects of theory and clinical care. Psychopathology helps students see the whole disorder--and the whole patient"--Provided by publisher.